Les formes de régulation de l'activité des élèves - Pier Carlo Bocchi (Nantes Université, 2012)
Some elements of a comparative study centered on reading and writing sessions are used to explain processes of shoring student activity developed by teachers. The study is conducted in 2 classes of primary school in the Italian part of Switzerland. In reference to the notion of pattern given by Gerard Vergnaud, we'll show how the teacher can, during the interaction, promote adjustment leading to the success (pragmatic regulation) rather than adjustment for understanding (epistemic regulation) that implies an interaction focused on the production of conceptualizations. In order to understand the activity of the teacher relevancy of procedures adopted depending on the student's abilities, our approach highlights the counterproductive and socially stigmatization nature of some teaching practices. In particular, the pragmatic and epistemic teachers adjustments are developed taking in relation with the status of students. Such practices can have the effect of amplifying difficulties of students less advanced and thus enhance the educational inequality.